USING THE MOST CONVENIENT METHOD OF FINDING EQUAL SIDED POLYGONS (By Dividing the Diameter into Equal Sections) - Israel Omandovlat ugli Jumayev (Galaxy International Interdisciplinary Research Journal, 2022)
The article shows how to use an effective method of explaining to students by dividing circles into equal parts.